PENGARUH ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN MELALUI INOVASI PRODUK (Studi pada UMKM Rogo-Rege Kabupaten Semarang) - Asa Ridho Nursinggih; Naili Farida (Universitas Diponegoro, 2019)
Rogo-Rege MSME is a handicraft industry in Semarang Regency with the largest number of craftsmen compared to other handicrafts. Rogo-rege has the potential to develop, but sales of logo-rege have fluctuated in the last 5 years. The purpose of this study is to determine the effect of market orientation and entrepreneurial orientation on marketing performance through product innovation in the Rogo-Rege MSME Semarang Regency. This type of research is explanatory research with data collection techniques through questionnaires and interviews. The sample of this study was 45 Rogo-Rege craftsmen in Semarang Regency with the criteria of having carried out business activities for at least 3 years. The analysis technique that was used is quantitative analysis with the help of PLS (Part Least Square). The results showed that there was a positive and significant influence on entrepreneurial orientation towards product innovation, market orientation towards marketing performance, and product innovation on marketing performance. The results of the study also showed a positive yet not significant effect on market orientation towards product innovation and entrepreneurial orientation towards marketing performance. The results of the indirect influence test indicate a positive and significant influence of entrepreneurial orientation on marketing performance through product innovation and the existence of a positive but insignificant influence of market orientation on marketing performance through product innovation.